Supply Chain Performance in the Manufacturing Sector: The Role of Lead-Time Management Strategies - Kimwaki, Benedict Mutinda (Journal Integration of Social Studies and Business Development, 2024)
The objective of this research was to evaluate the effectiveness of lead-time management strategies in influencing the operational efficiency of manufacturing enterprises. While prior studies have recognized lead time as a crucial factor impacting supply chain performance, scant attention has been paid to the specific contribution of lead-time management strategies in this context. Hence, this study aimed to bridge this gap. By employing a descriptive survey research design, data were collected from a sample of 153 manufacturing firms selected through purposive sampling. The primary data collection instrument was a structured questionnaire, and statistical analyses were conducted using SPSS software. The findings indicate that early involvement of suppliers in product design and dissemination of accurate customer specifications significantly reduces lead time. Process automation and efficient transport management, including route planning and vehicle scheduling, were found to enhance supply chain performance. Consequently, the study concludes that early supplier involvement, process automation, and effective transport management positively impact supply chain performance. Based on these findings, it is recommended that manufacturing companies prioritize initiatives aimed at reducing lead time, such as minimizing waiting times, engaging suppliers early in the process, automating processes, and improving transport management in order to enhance overall supply chain performance.